Perlindungan Hukum Kepemilikan Tanah dalam Sengketa Sertifikat Hak Atas Tanah di Desa Hinekombe, Kecamatan Sentani, Kabupaten Jayapura, Provinsi Papua (Putusan Perkara Nomor: 31/G/2023/PTUN.JPR) - Rere, M. Nurdin Eba; Suardi, Suardi (HUMANIORUM, 2025)
This article discusses one of the problems that often occurs in Indonesia, giving rise to legal uncertainty and conflict in society. This research discusses legal protection and judges' considerations regarding ownership of land rights in land title certificate disputes in deciding lawsuit cases at the State Administrative Court. The main focus of the research is to analyze the role of the National Land Agency (BPN) in preventing and resolving disputes, as well as the legal mechanisms adopted. The research method used is normative with a statutory approach and case studies. The research results show that holders of legally issued certificates do not necessarily have the right to obtain legal protection through a lawsuit to the State Administrative Court (PTUN) and settlement through mediation at BPN. Apart from that, implementing the principles of legal certainty and good faith in every certificate processing process is an important factor in avoiding disputes. This research recommends increasing supervision in the process of issuing land certificates and strengthening the technology-based land administration system to prevent future land ownership disputes.